DNA Methylation and mRNA Expression of OX40 (TNFRSF4) and GITR (TNFRSF18, AITR) in Head and Neck Squamous Cell Carcinoma Correlates With HPV Status, Mutational Load, an Interferon-γ Signature, Signatures of Immune Infiltrates, and Survival. Issue 4 (15th May 2022) - Loick, Sophia M.; Fröhlich, Anne; Gabrielpillai, Jennis; Franzen, Alina; Vogt, Timo J.; Dietrich, Jörn; Wiek, Constanze; Scheckenbach, Kathrin; Strieth, Sebastian; Landsberg, Jennifer; Dietrich, Dimo
Abstract : The tumor necrosis factor receptor superfamily members 4 (TNFRSF4, OX40) and 18 (TNFRSF18, GITR, AITR) are under investigation as targets for immunotherapy of various cancers, including head and neck squamous cell carcinomas. Understanding the regulation of OX40 and GITR, particularly on an epigenetic level, might help to develop companion predictive biomarkers. We conducted broad correlation analyses of DNA methylation of 46 CpG sites within the GITR / OX40 gene locus in head and neck squamous cell carcinomas and normal adjacent tissues provided by The Cancer Genome Atlas (TCGA) Research Network. We analyzed methylation levels with regard to transcriptional gene activity (mRNA expression), human papillomavirus (HPV) infection, differential methylation between tumors and normal adjacent tissues, signatures of immune cell infiltrates, an interferon-γ signature, mutational load, and overall survival. Moreover, we investigated methylation levels in HPV-positive and HPV-negative cell lines and in isolated monocytes, granulocytes, CD8 + and CD4 + T cells, and B cells from peripheral blood from healthy donors. Our results revealed a complex and sequence-contextual methylation pattern in accordance with features of epigenetic regulated genes. We detected significant methylation differences between normal adjacent and tumor tissues, between HPV-positive and HPV-negative tumors, between tumor and immune cells, and significant correlations between methylation and mRNA expression. We further found significant correlations of CpG methylation with overall survival, signatures of immune cell infiltrates, an interferon-γ signature, and mutational load. Our study provides a framework to prospectively test specific CpG sites as biomarkers, in particular in the context of immunotherapies.